2008
DOI: 10.1194/jlr.m800030-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Decreased iPLA2γ expression induces lipid peroxidation and cell death and sensitizes cells to oxidant-induced apoptosis

Abstract: Our previous studies showed that renal proximal tubular cells (RPTC) express Ca 21 -independent phospholipase A 2 g (iPLA 2 g) in endoplasmic reticulum (ER) and mitochondria and that iPLA 2 g prevents and/or repairs lipid peroxidation induced by oxidative stress. Our present studies determined the importance of iPLA 2 g in mitochondrial and cell function using an iPLA 2 g-specific small hairpin ribonucleic acid (shRNA) adenovirus. iPLA 2 g expression and activity were decreased in the ER by 24 h and in the mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
57
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 39 publications
3
57
0
Order By: Relevance
“…In renal proximal tubular cells, iPLA 2 ␥ removes oxidized phospholipids from the ER membrane during oxidative stress; thus, iPLA 2 ␥ may act to repair damaged lipids or prevent lipid peroxidation during oxidative stress (4). Consistent with these results, iPLA 2 ␥ knockdown in renal cells increased lipid peroxidation and induced apoptosis (6). Conversely, inhibition of microsomal iPLA 2 ␥ in rabbit renal proximal tubular cells during cisplatin-induced apoptosis reduced apoptosis markers, indicating that iPLA 2 ␥ contributes to apoptosis (7).…”
supporting
confidence: 75%
See 1 more Smart Citation
“…In renal proximal tubular cells, iPLA 2 ␥ removes oxidized phospholipids from the ER membrane during oxidative stress; thus, iPLA 2 ␥ may act to repair damaged lipids or prevent lipid peroxidation during oxidative stress (4). Consistent with these results, iPLA 2 ␥ knockdown in renal cells increased lipid peroxidation and induced apoptosis (6). Conversely, inhibition of microsomal iPLA 2 ␥ in rabbit renal proximal tubular cells during cisplatin-induced apoptosis reduced apoptosis markers, indicating that iPLA 2 ␥ contributes to apoptosis (7).…”
supporting
confidence: 75%
“…Up-regulation of such genes potentially enhances the chaperoning capacity of a cell, thereby alleviating adverse effects of protein misfolding and reducing cytotoxicity. Furthermore, it should also be considered that mechanisms other than ATF6 activation at the ER could contribute to iPLA 2 ␥ cytoprotection; for example, the action of iPLA 2 ␥ could involve reducing lipid peroxidation (4,6). In GECs, a portion of iPLA 2 ␥ was localized at the mitochondria (11).…”
Section: Transfection/treatment Rlumentioning
confidence: 99%
“…Considering that both eicosanoids and lysolipids mediate multiple cellular signaling pathways, the observed neurologic pathologies due to iPLA 2 ␥ ablation are not unanticipated and likely result from the accumulation of lipid substrates for iPLA 2 ␥ within the mitochondria. Alterations in mitochondrial membrane composition are likely associated with compromised mitochondrial function analogous to mitochondrial function observed in adenoviral-mediated short hairpin RNA iPLA 2 ␥ knockdown previously demonstrated in renal proximal tubular cells (47).…”
Section: Discussionmentioning
confidence: 99%
“…During oxidative stress, an ER-associated iPLA 2 in renal proximal tubular cells (iPLA 2 ␥) recognizes, cleaves, and removes oxidized phospholipids from the ER membrane (25); thus, iPLA 2 ␥ may act to repair or prevent lipid peroxidation during oxidative stress (25). Another study demonstrated that expression of shRNA against iPLA 2 ␥ increased lipid peroxidation and induced apoptosis in renal cells (26). iPLA 2 is involved in signal transduction pathways that include mitogen-activated protein kinase (MAPK) p38, epidermal growth factor (EGF) receptor, the tumor suppressor gene, p53, and cell cycle-regulator, p21 (27).…”
mentioning
confidence: 99%